2003
DOI: 10.1128/mcb.23.4.1163-1174.2003
|View full text |Cite
|
Sign up to set email alerts
|

Small Maf Compound Mutants Display Central Nervous System Neuronal Degeneration, Aberrant Transcription, and Bach Protein Mislocalization Coincident with Myoclonus and Abnormal Startle Response

Abstract: The small Maf proteins form heterodimers with CNC and Bach family proteins to elicit transcriptional responses from Maf recognition elements (MAREs). We previously reported germ line-targeted deficiencies in mafG plus mafK compound mutant mice. The most prominent mutant phenotype was a progressive maf dosage-dependent neuromuscular dysfunction. However, there has been no previous report regarding the effects of altered small-maf gene expression on neurological dysfunction. We show here that MafG and MafK are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
50
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 35 publications
8
50
0
Order By: Relevance
“…Since several neurodegenerative disorders are suspected to result from a dysregulated oxidative stress response, we analyzed the expression of ARE-dependent genes in the central nervous systems of these symptomatic mutant mice. These studies showed that the heme oxygenase 1 gene (HO-1) was induced in G0K1 compound mutant animals, whereas many other ARE-dependent genes were not significantly affected (16). We also found that Bach proteins failed to accumulate in neuronal nuclei in the G0K1 central nervous system, which could explain the observed HO-1 transcriptional derepression (16,42).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Since several neurodegenerative disorders are suspected to result from a dysregulated oxidative stress response, we analyzed the expression of ARE-dependent genes in the central nervous systems of these symptomatic mutant mice. These studies showed that the heme oxygenase 1 gene (HO-1) was induced in G0K1 compound mutant animals, whereas many other ARE-dependent genes were not significantly affected (16). We also found that Bach proteins failed to accumulate in neuronal nuclei in the G0K1 central nervous system, which could explain the observed HO-1 transcriptional derepression (16,42).…”
mentioning
confidence: 52%
“…Although mafF Ϫ/Ϫ (F0) and mafK Ϫ/Ϫ (K0) mice displayed no apparent mutant phenotypes, mafG-null mutant mice displayed mild thrombocytopenia accompanied by a late-onset neurological disorder (39). The neurological abnormality was exacerbated in mafG Ϫ/Ϫ ::mafK ϩ/Ϫ (G0K1) compound mutant mice, suggesting that MafG and MafK share compensatory functions in the central nervous system (16). Since several neurodegenerative disorders are suspected to result from a dysregulated oxidative stress response, we analyzed the expression of ARE-dependent genes in the central nervous systems of these symptomatic mutant mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, we concluded that small Maf proteins act cooperatively with Nrf2 to activate the transcription of these genes. In contrast, HO-1 transcription is derepressed in small maf compound mutant mice, similarly to the bach1-null mutant (16), suggesting that small Maf proteins are also important for collaboratively repressing HO-1. In this way, we genetically confirmed that small Maf proteins act as required cofactors in both positive and negative MARE-dependent regulation of gene transcription.…”
mentioning
confidence: 77%
“…However, it is also possible that small Maf proteins heterodimerize with Bach1 to form a transcriptional repressor. The Bach1-MafG heterodimer may repress mafG gene transcription through mafG Ic-ARE in the same way as it represses HO-1 gene expression (9,16). The contribution of Bach1 proteins to the regulation of mafG is under investigation.…”
Section: Discussionmentioning
confidence: 99%